2009
DOI: 10.1007/s00266-009-9396-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Risk of Systemic Fat Mobilization and Fat Embolus Following Liposuction with Dry and Tumescent Technique: An Experimental Study on Rats

Abstract: We found signs of fat embolus in both blood specimens and histological examinations of tissue samples in the study groups. However, the results of the examinations were normal in the control group. Although there were no fat particles in the blood before liposuction, blood specimens obtained following the procedures and in the long-term had fat particles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…Of these, 3 reported death after liposuction for esthetic purposes, and 2 of these reports were published in the last 5 years 13,16 . We also found 4 experimental studies on liposuction complications [18][19][20][21] . Unusual complications were as follows: 1 case of vascular injury with perforation of a large vessel during li po suction 9 ; 2 cases of intestinal perforation 22 ; 4 articles reporting severe bacterial infections after liposuction 23,24 ; 1 case of herpes zoster 25 ; 1 case of urethral injury 26 ; and 3 articles on vision loss associated with liposuction.…”
Section: Resultsmentioning
confidence: 73%
“…Of these, 3 reported death after liposuction for esthetic purposes, and 2 of these reports were published in the last 5 years 13,16 . We also found 4 experimental studies on liposuction complications [18][19][20][21] . Unusual complications were as follows: 1 case of vascular injury with perforation of a large vessel during li po suction 9 ; 2 cases of intestinal perforation 22 ; 4 articles reporting severe bacterial infections after liposuction 23,24 ; 1 case of herpes zoster 25 ; 1 case of urethral injury 26 ; and 3 articles on vision loss associated with liposuction.…”
Section: Resultsmentioning
confidence: 73%
“…It was observed that increasing the number of fat globules is directly related to the time of liposuction 11 . In our study, the liposuction procedure was performed on all animals at time of less than 10 minutes with removal of 8 ml of adipose tissue per animal, contrasting with the 60 minutes cited in other studies 11,12 . The lack of finding may also be attributed to the minimally invasive nature of the technique and choice for reduced surgical time.…”
Section: Discussionmentioning
confidence: 77%
“…In both groups were found FE with the exception of control group 12 . The use of tumescent technique involves the use of higher anesthetic infiltration and thus increases the risk of complications related to anesthesia.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations